EXPERIMENTAL AND THEORETICAL STUDY OF PRESSURE EFFECTS ON HYDROGEN ISOTOPE FRACTIONATION IN THE SYSTEM BRUCITE-WATER AT ELEVATED TEMPERATURES - Horita J.; Cole D.R.; Polyakov V.B.; Driesner T. (My University, 2002)
A detailed, systematic experimental and theoretical study was conducted to investigate the effect of pressure on equilibrium D/H fractionation between brucite (Mg(OH)2) and water at temperatures from 200 to 600°C and pressures up to 800 MPa. A fine-grained brucite was isotopically exchanged with excess amounts of water, and equilibrium D/H fractionation factors were calculated by means of the partial isotope exchange method. Our experiments unambiguously demonstrated that the D/H fractionation factor between brucite and water increased by 4.4 to 12.4‰ with increasing pressure to 300 or 800 MPa at all the temperatures investigated. The observed increases are linear with the density of water under experimental conditions. We calculated the pressure effects on the reduced partition function ratios (β-factor) of brucite (300–800 K and P ≤ 800 MPa) and water (400–600°C and P ≤ 100 MPa), employing a statistical-mechanical method similar to that developed by Kieffer (1982) and a simple thermodynamic method based on the molar volumes of normal and heavy waters, respectively. Our theoretical calculations showed that the reduced partition function ratio of brucite increases linearly with pressure at a given temperature (as much as 12.6‰ at 300 K and 800 MPa). The magnitude of the pressure effects rapidly decreases with increasing temperature. On the other hand, the β-factor of water decreases 4 to 5‰ with increasing pressure to 100 MPa at 400 to 600°C. Overall D/H isotope pressure effects combined from the separate calculations on brucite and water are in excellent agreement with the experimental results under the same temperature-pressure range. Our calculations also suggest that under the current experimental conditions, the magnitude of the isotope pressure effects is much larger on water than brucite. Thus, the observed pressure effects on D/H fractionation are common to other systems involving water. It is very likely that under some geologic conditions, pressure is an important variable in controlling D/H partitioning.